Knowledge, Attitude, and Possible Barriers of Dental Practitioners Regarding Child Abuse in Benghazi, Libya - Abdelnabi, Abdelmonem; Ibrahim Garoushi; Fathia Almajbari; Ali Alshukrey; Abdelmalik Alwerfally; Raghad Farkash (AlQalam Journal of Medical and Applied Sciences, 2025)
Child abuse can be understood as the intentional harm or mistreatment of a child under the age of 18. Notably, this can be in the form of physical, emotional, and sexual abuse. It can also be seen as neglect as well. To highlight, dental practitioners are healthcare professionals who interact with children frequently. Therefore, dentists play an important role in identifying and responding to signs of child abuse. In Libya, more research needs to be conducted into how dental practitioners are detecting and reporting cases of child abuse that occur during clinical practice. This study aims to evaluate the knowledge and attitude of dental practitioners in Benghazi, Libya, regarding child abuse, identify the barriers that prevent the reporting of suspected cases in practice, and to increase the awareness of that issue. This study was an observational cross-sectional study. The sample size consisted of 250 dental practitioners in Benghazi, Libya. Questionnaires were utilized for data collection. Data was sorted and collected through descriptive analysis. Findings illustrated that dentists in this sample would profit from completing more formal training on child abuse and how to report cases of child abuse in practice. This study also found that the major barriers faced when reporting child abuse cases were the fear of inflicting more harm on the child. Minimal research in Libya has been conducted to investigate the knowledge and attitudes of dentists about child abuse. Understanding healthcare professionals’ perceptions and reporting practices can increase awareness and improve future dental training programs on child abuse